THE DIFFERENT PERCEPTIONS AMONG MIDWIVES TOWARD POST C-SECTION WOMEN WITH HIV - Faridatul Ummi; Jimmy Yanuar Annas; Sulistiawati Sulistiawati (UNIVERSITAS AIRLANGGA, 2021)
AbstractBackground: Puerperal post Sectio Caesarea was the period of physical and psychological drain, especially with HIV (Human Immunodeficiency Virus) as complication. In general, health workers still discriminate against HIV patients, as well as post-sectio mothers with HIV. This situation add to the psychological burden and increases the risk of depression during the puerperium. Midwife’s perception in caring for post-Section mothers with HIV is needed to produce attitudes and behaviours in supporting care. This study aims to describe the perception of midwives in providing care to post-sectio patients with HIV. Method: This study used a qualitative approach in two HIV referral hospitals in Surabaya with different class types. Participants in this study were determined by purposive sampling, consisting of 6 participants and 4 triangulation participants. Researcher conducted in-depth interview and closed observation with instruments such as recorders, observation sheets and the researchers themselves. Data processing and analysis is carried out by data reduction, data presentation and conclusions. Result: Participants in Hospital ‘A’ did not provide different services to post SC patients with HIV while still applying universal precautions. Participants in Hospital ‘B’ think that special treatment is needed by applying exaggerated universal precautions. Conclusion: Midwives keep trying to provide comprehensive care although there are differences in perception.